2013
DOI: 10.5194/cpd-9-1397-2013
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Caspian Sea level changes during the last millennium: historical and geological evidences from the south Caspian Sea

Abstract: Historical literature may constitute a valuable source of information to reconstruct sea level changes. Here, historical documents and geological records have been combined to reconstruct Caspian sea-level (CSL) changes during the last millennium. In addition to a literature survey, new data from two short sediment cores were obtained from the south-eastern Caspian coast to identify coastal change driven by water-level changes. Two articulated bivalve shells from the marine facies were radiocarbon dated… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(21 citation statements)
references
References 52 publications
0
21
0
Order By: Relevance
“…Salinity of the surface waters is lowest ( c. 3‰ or less) close to the Volga outflow, increasing to around 13.5‰ in the central and southern basins (Kosarev and Yablonskaya, 1994). The surface of the Caspian Sea is currently about 26.5 m below global sea level (Arpe et al, 2012; Naderi Beni et al, 2013a) and not connected directly to the world’s oceans at the present time, although connections are known to have occurred in the recent geological past. A marine connection existed at the end of the Pliocene to beginning of the Pleistocene (Akchagylian stage) between c. 3.2 and 2 million years ago (Kosarev and Yablonskaya, 1994; Van Baak et al, 2013), and connections were re-established at various times throughout the Pleistocene (Badertscher et al, 2011; Forte and Cowgill, 2013; Rychagov, 1977; Tudryn et al, 2012).…”
Section: The Study Areamentioning
confidence: 99%
See 3 more Smart Citations
“…Salinity of the surface waters is lowest ( c. 3‰ or less) close to the Volga outflow, increasing to around 13.5‰ in the central and southern basins (Kosarev and Yablonskaya, 1994). The surface of the Caspian Sea is currently about 26.5 m below global sea level (Arpe et al, 2012; Naderi Beni et al, 2013a) and not connected directly to the world’s oceans at the present time, although connections are known to have occurred in the recent geological past. A marine connection existed at the end of the Pliocene to beginning of the Pleistocene (Akchagylian stage) between c. 3.2 and 2 million years ago (Kosarev and Yablonskaya, 1994; Van Baak et al, 2013), and connections were re-established at various times throughout the Pleistocene (Badertscher et al, 2011; Forte and Cowgill, 2013; Rychagov, 1977; Tudryn et al, 2012).…”
Section: The Study Areamentioning
confidence: 99%
“…Subsequently, it is generally agreed that Caspian Sea levels were variable, but mostly high, in the early to mid-Holocene with maximum levels of around −24 to −20 m below present-day global sea level ( c. 3–7 m above present-day levels) between c. 9000 and c. 5000 years ago (Chepalyga, 2007; Rychagov, 1997). Further highstands then occurred, with Caspian Sea levels reaching −25 to −19 m below present-day global sea level (Naderi Beni et al, 2013a, 2013b) within the last few hundred years, following a late Holocene lowstand event known regionally as the Derbent. Overeem et al (2003) showed how the very recent sediments and vegetation in the Damchik region have evolved over a period of (mainly) sea level fall since 1935, based on aerial photographs and vegetation maps.…”
Section: The Study Areamentioning
confidence: 99%
See 2 more Smart Citations
“…These dramatic sea level changes have affected the surrounding populations and their activities. The Italian traveller Marin Sanudo already documented that the early 14th-century water-level rise destroyed many important cities around the CS (see Naderi Beni et al, 2013a). The recent and rapid CSL changes have directly affected tens of thousands of people in the lowlands of Iran, Azerbaijan, Dagestan and the Volga Delta (Rucevska et al, 2006).…”
Section: Introductionmentioning
confidence: 99%